2023
DOI: 10.3390/su15032660
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Issues in Fitness Centers through News Articles before and after the COVID-19 Pandemic in South Korea: Applying Big Data Analysis

Abstract: This study aimed to identify major topics and trends of media reports in news articles related to fitness centers before and after COVID-19 using big data analysis and to suggest future improvements. We collected 20,528 news articles from 2018 to 2019 (pre-COVID-19) and 20,264 news articles from 2020 to 2021 (post-COVID-19) and conducted frequency analysis, topic modeling, and sentiment analysis. The top keywords related to fitness centers were fitness, health, healthcare, and center both before and after COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, previous studies have shown that the presence of COVID-19 has been shown to influence the decision-making process [ 32 , 33 ]. In addition, gyms or fitness centers were considered places with a high risk for COVID-19 virus transmission [ 34 ]. On the other hand, previous studies have also shown that exercise can improve the immune system by increasing the number of immune cells and strengthening the body’s defenses against the virus, thus providing a cost-effective, practical, and non-pharmacological way to deal with COVID-19 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that the presence of COVID-19 has been shown to influence the decision-making process [ 32 , 33 ]. In addition, gyms or fitness centers were considered places with a high risk for COVID-19 virus transmission [ 34 ]. On the other hand, previous studies have also shown that exercise can improve the immune system by increasing the number of immune cells and strengthening the body’s defenses against the virus, thus providing a cost-effective, practical, and non-pharmacological way to deal with COVID-19 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past 3 years, fitness centers have experienced a sharp decline in sales and a decrease in the number of centers the government's social distancing and indoor sports facility restrictions during COVID-19 [ 12 ]. Fortunately, with the recent ending of the pandemic, there has been a heightened interest in health more than before the pandemic, leading to a recovery in the market conditions of fitness centers [ 13 ]. McKinsey & Company noted that the fitness industry is bouncing back with significant increase in revenue, and experts predict the industry will grow by 171.75 % between now and 2028 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%